Point shear wave elastography (pSWE) using Acoustic Radiation Force Impulse (ARFI) imaging: a feasibility study and norm values for renal parenchymal stiffness in healthy children and adolescents - Grass, Lilian; Alrajab, Abdulsattar; Bui, Thi-Thanh-Tam; Hoffmann, Georg F.; Wühl, Elke; Schenk, Jens-Peter (Medical ultrasonography, 2017)
Aims: To evaluate the applicability of point shear wave elastography (pSWE) for measuring renal parenchymal stiffness in healthy children and adolescents and to establish norm values for shear wave speed (SWS) using two ARFI methods and ultrasound probes.Material and methods: We prospectively investigated 264 children (43.9% males). pSWE (Virtual TouchTM Quantification and Virtual TouchTM Imaging Quantification (VTQ and VTIQ; Siemens, Germany)) was performed in the renal cortex of 528 healthy kidneys using a 1-6 MHz convex and a 4-9 MHz linear ultrasound probe in ventrolateral and dorsal examinations. Feasibility and reproducibility of pSWE measurements were evaluated. SWS values were analysed with regard to age, body dimensions, kidney volume and measuring depth.Results: pSWE measurements were successful in >95% of subjects using the low and in <60% using the high-frequency probe. Mean SWS values (m/s) differed by method and probe: 2.10±0.43 (VTQ1-6MHz, convex, ventrolateral), 2.30±0.37 (VTQ1-6MHz, convex, dorsal), 1.58±0.44 (VTQ4-9MHz, linear, dorsal) and 1.96±0.27 (VTIQ4-9MHz, linear, dorsal). SWS was positively correlated with age, weight and body height, but independent of sex, BMI, or kidney volume and depth.Conclusions: pSWE (VTQ) is a feasible method to evaluate renal parenchymal stiffness in children of all ages. SWS values are age and weight dependent and differ significantly between high- and low-frequency probes. High-frequency probes and VTIQ should only be used in children <10 years.
Gesehen am 03.05.2018